2000
DOI: 10.1159/000014470
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Kinetics in Blood during Haemodialysis and in vivo Clearance of Inorganic Phosphate

Abstract: Contradictory data are reported in the literature concerning the diffusion kinetics of inorganic phosphates (iPh) between red blood cells and plasma during haemodialysis. Accordingly, we performed mass balance and equilibration studies to analyze the diffusion kinetics of iPh in vivo and in vitro. Mass balance analysis shows that iPh is only cleared from the plasma volume and thus that it practically does not diffuse from red blood cells to plasma during the short time lapse of blood transit through the haemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…There is another technical problem in assessing dialyzer phosphate clearance that was highlighted by Descombes et al 37 They showed that when measuring dialyzer phosphate clearance in vivo, the outlet blood sample needs to be centrifuged right away, as otherwise, there is delayed entry of phosphate from RBCs into plasma, artefactually elevating the plasma concentration. This does not affect the manuscript calculations directly, but in a number of studies where clearances were calculated, this may cause marked underestimation of dialyzer phosphate clearance.…”
Section: Discussionmentioning
confidence: 99%
“…There is another technical problem in assessing dialyzer phosphate clearance that was highlighted by Descombes et al 37 They showed that when measuring dialyzer phosphate clearance in vivo, the outlet blood sample needs to be centrifuged right away, as otherwise, there is delayed entry of phosphate from RBCs into plasma, artefactually elevating the plasma concentration. This does not affect the manuscript calculations directly, but in a number of studies where clearances were calculated, this may cause marked underestimation of dialyzer phosphate clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The mean intracellular phosphate efflux rate did not exceed 362 μmol/kg/hr. A more recent mass balance analysis showed that phosphate is only cleared from the plasma volume, and that it does not diffuse from red blood cells to plasma during the short time lapse of blood transit through the hemodialyzer [40].…”
Section: Relevance Of the Emerging Daily Dialysis Experiencementioning
confidence: 99%
“…Thus, on the basis of diffusion alone, phosphorus removal from an aqueous solution across a dialysis membrane should be somewhere between that of urea and creatinine. However, while urea is removed from both plasma and red blood cell water during dialysis, phosphorus, like creatinine, is removed primarily from the plasma space (7), although in one relatively recent study, some removal from red blood cells appeared to be present (8). This markedly reduces phosphorus clearance relative to urea for any level of whole blood flow rate, an effect that is magnified in patients with high levels of hematocrit (3).…”
mentioning
confidence: 99%